Peran Pemerintah Desa Dalam Meningkatan Pemberdayaan Masyarakat Desa Kasango Kecamatan Taliabu Barat Laut Kabupaten Pulau Taliabu Propinsi Maluku Utara - S, Sarman; Tohopi, Rustam; Nani, Yacob Noho (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the role of the Kasango Village Government, Pulau Taliabu Regency, in enhancing community empowerment through four key roles: regulator, dynamizer, facilitator, and catalyst. This research employs a qualitative approach with data collection techniques including interviews, observation, and documentation. The findings indicate that the government's role as a regulator is not yet optimal due to the absence of comprehensive village regulations. As a dynamizer, the village government has encouraged community participation through financial incentives and skill training programs based on local potential; however, this participation remains temporary. As a facilitator, the village government has provided basic infrastructure and direct cash assistance, but poor maintenance of infrastructure remains a major obstacle. Meanwhile, as a catalyst, the village government has allocated funds to the fisheries and agriculture sectors, though these efforts have not been followed by adequate mentoring. Therefore, improvements in regulation development, increased community participation, and program mentoring are necessary to ensure sustainability and effectiveness. Additionally, alternative funding sources are needed to overcome budget limitations.